Phytophthora Infestans Induced Gene Expressional Changes in Different Potato Cultivars - Tran Dinh, Quyen; Taller, János; Nagy, Erzsébet; Mészáros, Melinda; Polgár, Zsolt; Wolf, István; Frank, Krisztián (GEORGIKON FOR AGRICULTURE, 2024)
The oomycete fungus Phytophthora infestans is the most damaging pathogen of potatoes. Sources of resistance are identified in different wild potato species, and some of these genes have already been isolated. During the six decade long resistance breeding program in Keszthely, race-specific P. infestans resistance genes were used in breeding. One of these cultivars, White Lady (WL), was used in this study together with the susceptible Sárvári borostyán (Sb) and Kastia (K) for transcriptomic analysis. Purpose of the present experiment was to analyse the Phytophthora inoculation induced stress response in the three varieties. Transcriptomes were reconstructed from samples collected 18, 24, 48 and 72 hours after inoculation. The results clearly revealed, that in the resistant WL significantly more genes, in some cases three-five times more genes are upregulated, than in the two susceptible cultivars. Similarly, significantly more genes are downregulated in the WL, than in Sb or K. It is concluded that the response to P. infestans inoculation is more comprehensive in the resistant cultivar, and possibly this reorganisation of tens of thousands of functioning genes leads to a successful resistance response. This process is suggested to be triggered by the race-specific late blight resistance genes in White Lady.
Keywords: Phytophthora infestans; late blight; potatoes; resistance; transcriptomes